2011
DOI: 10.1016/j.cell.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Translocation Sequencing Reveals Mechanisms of Chromosome Breaks and Rearrangements in B Cells

Abstract: The Supplemental Information files of the Gro-Seq data that were used to generate parts of Figures 5-7 and their related supplemental figures were inadvertently omitted from the initial Supplemental Information. The Gro-Seq data sets are deposited in SRA (http://www.ncbi.nlm.nih.gov/sra) under accession number SRA049000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
175
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(184 citation statements)
references
References 0 publications
7
175
2
Order By: Relevance
“…Accumulating data suggest that AID-dependent DNA damage seems to be one of the major driving forces for variable types of mature B cell-derived lymphomas (47)(48)(49). In the absence of factors from the HR pathway, off-target activity of AID seems to be able to generate numerous non-Ig locus DNA DSBs, dramatically increasing genome instability and B cell cytotoxicity (14).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data suggest that AID-dependent DNA damage seems to be one of the major driving forces for variable types of mature B cell-derived lymphomas (47)(48)(49). In the absence of factors from the HR pathway, off-target activity of AID seems to be able to generate numerous non-Ig locus DNA DSBs, dramatically increasing genome instability and B cell cytotoxicity (14).…”
Section: Discussionmentioning
confidence: 99%
“…DSBs around transcription start sites (TSSs) have been implicated in the transcriptional activation of nuclear hormone receptor genes in tumor cell lines (5,6) and are required for the transcription of a set of early-response genes in activated neurons in culture (7). We also have found that activated B cells in culture generate genomic DSBs at active TSSs, as measured by global nuclear run-on sequencing (GRO-seq) (8) and that these TSS-associated DSBs can translocate to recurrent "bait" DSBs introduced in the body of the c-Myc gene (9).…”
mentioning
confidence: 93%
“…We previously developed an unbiased, high-throughput, genomewide, translocation sequencing (HTGTS) approach to identify DSBs via their translocation to bait DSBs at defined genomic sites in primary progenitor and activated mature B cells, NSPCs, and human cell lines (4,9,(26)(27)(28). Because of cellular heterogeneity in 3D genome organization (3,27,29), HTGTS detects, with great sensitivity, recurrent DSBs in any given genomic location (4,9,(26)(27)(28)(29) or recurrent classes of DSBs, such as DSBs at TSSs, that may occur at much lower frequency in any given location (ref.…”
mentioning
confidence: 99%
“…For example, rrm3 mutant has the same GCR rate as the wild type despite the known role of Rrm3 in preventing replication stalling at hard-to-replicate sites, possibly due to the lack of such sites in the 12-kb region monitored by the GCR assay (Schmidt and Kolodner 2006). Recently, deep sequencing-based methods have been employed to simultaneously identify tens of thousands of translocation junctions without growth selection (Chiarle et al 2011;Klein et al 2011). These approaches rely on an artificial DSB to induce and map translocations and thus are still not bias free.…”
Section: Comparison With Other Methods That Can Reveal Dna Lesion Hotmentioning
confidence: 99%